PERCEPTION OF ADULTS TOWARDS MEN IN NURSING IN CALABAR MUNICIPALITY CROSS RIVER STATE, NIGERIA - ella, regina etita (Advances in Social Sciences Research Journal, 2018)
Nursing despite its advancement, is still widely perceived to be a “female profession”. Globally, this perception has made recruitment and retention of qualified young men into the profession a worldwide challenge. Nigeria is no exception. Understanding the perception of adults about men in nursing will help in identifying misconceptions and information that could be helpful in planning public enlightenment about the profession Objective: To explore the perception of adults towards men in nursing in Calabar municipality of Cross River State, Nigeria. Methods: A self-structured questionnaire was administered to 196 adult men and women selected through purposive sampling. Results: Of the 196 respondents, 169(83.3%) were between the ages of 20-29 years, only 27 (13.8%) were aged 30 and above. Considering gender, male and female were 98(50%) each. Majority 175 (89.5%) were single. 146 (74.5%) had tertiary education whereas 34(17.4%), 2(1%) and 14 (7.1%) had secondary, primary and no education respectively. The result further showed that adults in Calabar municipality have a negative perception of men in nursing: men in nursing are not as skilful in giving care as women 172(87.4%), men become nurses because they are under achievers 132(67.3%), men in nursing are less compassionate 115 (58.7%) Society’s’ perception of a man’s touch to be sexual 152(77.6%). society’s consideration that nursing is feminine 109 (55.6%) and Negative mass media adverts 104(53.0%), were factors that influenced the negative perception of men in nursing. Conclusions: Adults in Calabar Municipality seems to have a negative perception about men in nursing and this reflects in the limited attraction of men into the nursing profession, even though they appreciate it. These negative perceptions are fuelled by factors such as societal beliefs about nursing and the mass media. There is need to enlighten the public to see nursing as a profession as any other profession that can be practiced by both males and females through public lectures, mass media and projection of nursing roles as both feminine and masculine. Future research is indeed warranted to investigate other key factors that may influence the overall male perception toward the profession of nursing and the impact of these in nursing profession.